Optimization of private label product marketing strategy with brand image analysis and product quality in indomaret trbv1436 palembang consumer purchase decisions - Oktavianti, Santi; Rahmania, Vanesha; Kurniawan, Anton; Ruhmana, Hariyati; Romi, Kms. (Institute of Computer Science (IOCS), 2024)
This study aims to test empirically how the influence of brand image and product quality on purchasing decisions, then to see how much brand image and product quality influence purchasing decisions for private label products at Indomaret TRBV1436 Palembang. Quantitative research method using Likert scale measurement questionnaire data collection techniques. The population of this study were consumers of Indomaret TRBV1436 Palembang in the last four months with a sample size of 395 people using the slovin sampling technique. The data analysis technique in this study used the Structural Equation Model- Partial Least Square (SEM-PLS). The results show that both simultaneously and partially brand image and product quality have a positive and significant effect on purchasing decisions for private label products